Law Policy Implementation as the Determinant of the Legal Development of Society - Bakardzhiev Ya. V. (Vestnik Omskoj Ûridičeskoj Akademii, 2015)
The article focuses on the forms and mechanism of implementation of law policy, aspects of its interaction with different legal and social factors and determinants specifying its formation and enforcement.